THE COMPATIBILITY OF MODEL FOR LOW SHEAR FLOW ANALYSIS IN DEVELOPING PLASTICIZED HTPB-BASED BINDER - Afni Restasari; Luthfia Hajar Abdillah; Retno Ardianingsih; Bagus Wicaksono; Rika Suwana Budi (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
In developing flow behavior of plasticized prepolymer as liquid content of composite solid propellant, zero shear viscosity (ZSV) is a critical parameter that Goh-Wan equation is developed to model it recently [1]. Thus, this work aims to analyze the compatibility of the Goh-Wan equation toward the liquid content of propellant, characterize it, and determine the limit. In this work, a varied flow behavior index was obtained by using Hydroxy terminated polybutadiene (HTPB) and HTPB-DOA (Dioctyl adipate) system with the variable of its concentration, pre-heating, and pre-stirring methods as samples. Viscosity was measured at 2, 3, 4, and 5 rpm by using the disc spindle of Brookfield viscometer. For the minimum shear-rate investigation, as a limit of compatibility, other three sets of shear rates are applied, which are 0.6 – 5 rpm, 1 – 5 rpm, and 1,5 – 5 rpm. By functioning Goh-Wan equation (model 1) and Power-Law (model 2), a model was categorized as compatible if yields lower value of ZSV than the first experimental measured viscosity (η1st). Characterization was determined by a graph of plotting percentage difference of ZSV obtained from models 1 and 2 towards the index of flow behavior. The 3% of the difference between ZSV obtained from model 1 and η1st was set to be a minimum value for a set of applied shear-rate to be acceptable. It is reported that the Goh-Wan model is compatible with the liquid content of propellant and characterized by a perfect linear correlation. It is also found that a minimum applied shear rate of 1.5 rpm is acceptable for model compatibility.